World experience of green building – opportunities and threats for ukrainian developers - Skakun , Volodymyr; Khokhlin, D. (Ways to Improve Construction Efficiency, 2024)
The article is devoted to the study of the world experience in the development of the Green Building concept and its impact on the transformation of the Ukrainian development market. In the current conditions of global climate challenges and the strengthening of international environmental standards, sustainable development of construction is becoming one of the key factors in the competitiveness of development companies. Analysis of international practical certifications, such as LEED, BREEAM, DGNB and HQE, allowed to develop basic principles of ecological design, focused on energy efficiency, reducing the carbon footprint, rational use of resources and creating a comfortable environment for users. The study showed that in Ukraine these systems are only progressing and are integrated, but they demonstrate significant potential for attracting foreign investment and integration into the European economic space. The conducted SWOT analysis allows to identify key opportunities for the implementation of Green Building: the development of public-private partnerships, the formation of a domestic market for ecological materials, access to "green" financing and increasing the market value of certified objects. At the same time, a number of threats and barriers have been identified, including the high cost of certification and construction, an insufficient number of trained specialists, problems of harmonizing national standards with international requirements, as well as the risks of superficial application of the concept (“greenwashing”). The article proves that the strategic development of Ukrainian development companies requires a comprehensive approach, which includes the adaptation of international methods to local conditions, the creation of financial support mechanisms and the formation of innovative materials. The application of global experience in Green Building will contribute to increasing the competitiveness of Ukraine at the international level, while reducing environmental and social risks.